Marker‐assisted simultaneous but stepwise backcross breeding for pyramiding blast resistance genes Piz5 and Pi54 into an elite Basmati rice restorer line 'PRR78'. Issue 5 (7th June 2013) - Singh, Vikas K.; Singh, Atul; Singh, S. P.; Ellur, Ranjith K.; Singh, Devinder; Gopala Krishnan, S.; Bhowmick, P. K.; Nagarajan, M.; Vinod, K. K.; Singh, U. D.; Mohapatra, T.; Prabhu, K. V.; et al.
Abstract Marker‐assisted simultaneous but stepwise backcross breeding (MASS‐BB) was utilized in the present study for pyramiding blast resistance genes, Piz5 and Pi54, from non‐Basmati donors, C101A51 and Tetep, respectively, into PRR78, an elite Basmati restorer line of rice hybrid, Pusa RH10. Marker‐assisted foreground selection coupled with stringent phenotypic selection and background analysis was carried out for hastening the recovery of recurrent parent phenome (RPP) and genome (RPG) in two separate backcross series to produce BC2F1 plants with individual blast resistance gene. The best BC2F1 plant from each backcross series was intercrossed, and the resultant F1 was selfed to pyramid both blast‐resistance genes into PRR78. The plants homozygous for both the genes in the F2 were advanced through pedigree selection to produce superior blast‐resistant F5 lines. Background analysis revealed that the RPG recovery was up to 91.6%. Improved versions of Pusa RH10 developed using the improved PRR78 lines (PRR78+Piz5+Pi54) performed on par with the original Pusa RH10 and showed resistance to blast disease both under artificial screening and at hot spot locations.